2011
DOI: 10.1097/qai.0b013e3182167516
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Responses to Pneumocystis Proteins in HIV Patients With and Without Pneumocystis jirovecii Pneumonia

Abstract: Background Immune responses to Pneumocystis jirovecii are not well understood in HIV infection, but antibody responses to proteins may be useful as a marker of Pneumocystis risk or presence of Pneumocystis pneumonia (PcP). Design Retrospective analysis of a prospective cohort Methods Enzyme-linked immunosorbent assays of antibodies to recombinant Pneumocystis proteins of major surface glycoprotein fragments (MsgC1, C3, C8, and C9) and of antibody titers to recombinant kexin protein (KEX1) were performed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 40 publications
1
51
1
Order By: Relevance
“…These experimental studies are supported by a recent human study in which plasma anti-Kex and anti-Msg IgG levels were evaluated in HIV-infected patients with PCP and those with another AIDS-defining illness, both before and after their AIDSdefining illness (102). Antibody titers to Pneumocystis Msg and Kex increased after acute PCP, but low baseline Kex levels were associated with subsequent development of PCP, even in persons not yet at risk for PCP by CD4 cell count criteria.…”
Section: Pneumocystis Antigenssupporting
confidence: 50%
See 2 more Smart Citations
“…These experimental studies are supported by a recent human study in which plasma anti-Kex and anti-Msg IgG levels were evaluated in HIV-infected patients with PCP and those with another AIDS-defining illness, both before and after their AIDSdefining illness (102). Antibody titers to Pneumocystis Msg and Kex increased after acute PCP, but low baseline Kex levels were associated with subsequent development of PCP, even in persons not yet at risk for PCP by CD4 cell count criteria.…”
Section: Pneumocystis Antigenssupporting
confidence: 50%
“…HIV-infected patients with active PCP have significantly higher antibody titers to MsgC than patients with pneumonia due to other causes (68). Recent studies have supported the utility of MsgC titers as indicators of acute or recent PCP (102).…”
Section: Pneumocystis Antigensmentioning
confidence: 91%
See 1 more Smart Citation
“…This is important since it is possible that circulating antibody can be maintained long after CD4 T cells have been compromised. In fact, Gingo et al found that elevated antibodies specific for the P. jirovecii kexin protein (KEX1) were associated with reduced risk for developing PCP in human immunodeficiency virus (HIV)-infected individuals (9). Most papers addressing immunization or vaccine development have utilized animal models of infection, including mice, rats, ferrets, and nonhuman primates.…”
mentioning
confidence: 99%
“…Some of this antibody response is directed against major surface glycoproteins of the organism (16), and now that we have draft genomes for the mouse, rat, and human organisms, this family of major surface glycoproteins is the most divergent between the fungal species. This may explain the host specificity of these organisms (rat Pneumocystis does not infect mice, and vice versa), similar to what has been elegantly reproved with other host-specific commensals, such as segmented filamentous bacteria (17).…”
mentioning
confidence: 99%